Psikoedukasi Emosi dalam Meningkatkan Social Awareness Pemuda Remaja Gereja di Era VUCA - Mengga, Ruth Caroline; Ria, Natal; Mengga, Maria Josephine; Hermanto, Yanto Paulus (Real Coster : Jurnal Pengabdian kepada Masyarakat, 2024)
Life in the Vuca era demands sensitivity to rapid changes, including sensitivity in social relations because friction and harsh competition in life make social problems increase. This kind of thing is very likely to be experienced also by church youth. Due to biological factors, at the age of youth, teenagers are very vulnerable to emotional outbursts that can result in the disruption of their relationships with others. Understanding the Word of God about self-control needs to be accompanied by proper education so that the results are maximized it is very important to have emotional education to improve social awareness skills obtained by managing emotions correctly, to minimize conflict in the face of instability in the Vuca era. No emotion is useless, but emotions need to be managed so as not to damage. Therefore, emotional psychoeducation is needed to help recognize emotions and manage them properly. Emotional psychoeducation using quizzes and real-life illustrations and techniques for managing emotions will be very useful in responding to spontaneous emotions to avoid destructive emotional outbursts, including damaging social relationships. Keywords: emotion psychoeducation; social awareness; vuca; church youthAbstrakKehidupan di era Vuca menuntut kepekaan terhadap perubahan yang cepat, termasuk juga kepekaan dalam relasi sosial karena gesekan dan persaingan hidup yang keras membuat masalah sosial meningkat. Hal seperti ini sangat mungkin dapat dialami juga oleh pemuda remaja gereja. Karena faktor biologis, di usia pemuda remaja sangat rentan meledak secara emosi yang dapat mengakibatkan terganggunya relasi dirinya dengan orang lain. Pemahaman Firman Tuhan tentang penguasaan diri, perlu dibarengi dengan pendidikan yang tepat, agar hasilnya maksimal sehingga penting sekali pendidikan emosi untuk meningkatkan kemampuan social awareness yang didapat dengan pengelolaan emosi yang benar, sehingga dapat meminimalkan konflik dalam menghadapi ketidastabilan di era Vuca. Tidak ada emosi yang tidak berguna, tetapi emosi perlu dikelola agar tidak merusak. Sebab itu diperlukan psikoedukasi emosi yang bermanfaat membantu mengenali emosi serta dapat mengelolanya dengan baik. Psikoedukasi emosi dengan menggunakan kuis serta ilustrasi nyata dan teknik mengelola emosi akan sangat berguna dalam respon emosi spontan sehingga dapat menghidarkan diri dari ledakan emosi yang merusak, termasuk merusak relasi sosial.Kata Kunci: Psikoedukasi Emosi; Kepekaan Sosial; Vuca; Pemuda Remaja Gereja